Evaluasi Efektivitas Program Pembelajaran Hybrid Pasca Pandemi COVID-19 Dan Pengembangan Website Pembelajaran Online - Arifin, Agus (Jayapangus Press, 2024)
During the pandemic, educational institutions closed schools, campuses and the learning process was carried out without face-to-face in class, then along with the pandemic disaster, many innovators created learning facilities without having to be in classrooms by utilizing information technology, namely internet connections with computer networks. The goal is to take advantage of the advantages of both methods. Hybrid learning has advantages and disadvantages, namely: (1) Flexibility: Provides convenience for students to arrange learning schedules according to their needs; (2) Diverse learning experiences: Combining traditional approaches and the latest technology; (3) Digital skills development: Encourage learners to be more skilled in using technology. The research method used is research and development (R & D), which is a basic research activity to obtain information on user needs (needs assessment), then continued with development (development). From the analysis of the data obtained, that the hybrid learning program (combination) of online and face-to-face learning in the classroom has a positive effect on learning outcomes. The hybrid learning method, which integrates aspects of online with face-to-face learning, remains relevant even outside of pandemic conditions with various justifications. Hybrid learning programs, which combine online and face-to-face learning, have a positive influence on learning outcomes. Hybrid learning offers a variety of advantages, including flexibility, enriching learning experiences, adapting to student needs, mastery of technology, preparation for the future, personalized learning, balance of life and learning, cost and resource savings, and promoting collaboration and networking.